P–280 Changes in oolemma height during ICSI injection on day 0 is associated with day 5–6 blastocyst formation. (6th August 2021) - Jain, R; He, P; Jaques, C; Chambost, J; Ley, S; Patel, R; Arshad, A; Bihani, U; Kotrotsou, M; Hickman, C
Abstract: Study question: Does the oolemma response to ICSI injection on day 0 affect blastocyst formation on day 5–6 (d5/6)? Summary answer: A large change in oolemma height during ICSI injection on day 0 is associated with lower blastocyst formation rates on d5/6. What is known already: The oolemma changes in all dimensions (i.e. height, width and depth) and can exhibit different reactions in ICSI during needle injection. This is seen as instant rupture or with little needle pressure, normal rupture with the needle pushed approximately halfway through, or difficult rupture with repeated attempts or the needle passing 3/4 of the oocyte width. Previous studies have shown that these responses can affect degeneration and fertilisation rates on day 1, however, there is little research on its effect on blastocyst formation rates. Furthermore, most previous studies have used qualitative methods to assess oolemma response. Study design, size, duration: This is a retrospective study using ICSI procedure videos conducted by four embryologists in a private clinic from 2013–2015. All videos of procedures which did not result in 2PN or in which the oocyte was not fully visible were excluded. Six operators categorised 455 videos (by majority vote) into four groups based on the oolemma response: oolemma breakage within 1/4, between 1/4 and 1/2, between 1/2 and 3/4 and beyond 3/4 of the oocyte's width. Participants/materials, setting, methods: A U-Net neural network model was trained to extract the frame of maximum oolemma indent from each video which were validated by a human operator; any in which maximum indent occured after breaking of the oolemma were excluded. The ratio of starting to maximal indent width/height were calculated automatically and human-validated. Chi-squared tests were performed for each ratio vs d5/6 blastocyst formation. These results were compared with those obtained from purely human annotations. Main results and the role of chance: From the purely human annotations, the percentages of oocytes in groups 1–4 respectively were: 3.3%, 85.3%, 11.4% and 0%. This variation in oolemma response may be due to the arrangement of thick and thin microfilaments or cortical granules in the cytoskeleton. When analysed with d5/6 blastocyst formation, these showed no significant result (p = 0.12) which is consistent with findings using the model. The artificial intelligence (AI) model processed 26 frames per second. During human validation of the ratios calculated at maximal indentation, 36% of width ratios and 31% of height ratios were rejected. The proportion of blastocysts formed in the upper and lower quartile for each ratio was analysed. Both the upper (0.49) and lower (0.41) quartiles of the width ratios were not significant for d5/6 blastocyst formation. The lower (1.12) quartile of height ratios showed no significance, however there were significantly fewer blastocysts formed on d5/6 for the upper (1.18) quartile of height ratios (p < 0.025). This subtle change in the height ratio, which was significant for d5/6 blastocyst formation was not taken into account when grouping oocytes any previous literature (and our human labelling). Limitations, reasons for caution: This study was conducted at a single clinic so variations between clinics were not captured in the study and would need further collaborations to confirm the proportion of oocytes responses. Due to the small sample size, this study also did not identify any group 4 oocytes cultured until d5/6. Wider implications of the findings: The grouping criteria in this study were more quantitative than previous work yet indicated no correlation between the oolemma group and d5/6 blastocyst formation. However, changes in the height which are hard to assess in real-time (and which have been neglected in previous literature) were seen to be significant. Trial registration number: NA